Filesystems performance in GNU/Linux multi-disc data storage - Smoliński, Mateusz (Wydawnictwo Politechniki Łódzkiej, 2014)
This paper introduces research results of I/O performance for modern filesystems configured on multi-disk storage configuration in GNU/Linux operating system. Filesystem performance tests include basic file operations statistics depending on local disks management software RAID or logical volume manager LVM. The results allow to choose the appropriate filesystem to data storage space configuration in GNU/Linux, that provides bests performance.